Presentation and management of acute hypertriglyceridemic pancreatitis in pregnancy: A case report. (December 2015) - Lim, Rachel; Rodger, Sheila J; Hawkins, T Lee-Ann
Pancreatitis related to hypertriglyceridemia can occasionally occur during pregnancy, particularly if there are underlying genetic abnormalities in lipid metabolism. We report the case of a 27-year-old female with hypertriglyceridemic pancreatitis in pregnancy that was treated initially with lipid lowering medications, followed by plasma exchange for persistently elevated triglyceride levels. Despite multiple interventions, she developed recurrent pancreatitis and simultaneously had a preterm birth. In this case report, we highlight the various therapies and the use of plasmapharesis in secondary prevention of hypertriglyceridemic pancreatitis in pregnancy.